2009
DOI: 10.1038/sj.bjc.6604943
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitisation of U87MG brain tumours by anti-epidermal growth factor receptor monoclonal antibodies

Abstract: As epidermal growth factor receptor (EGFR) has been reported to be a radiation response modulator, HER inhibitors are regarded to act as potential radiosensitisers. Our study examined the role of nimotuzumab and cetuximab both, the two monoclonal antibodies (mAbs) to EGFR, as radiosensitisers in a murine glioma model in vivo. Co-administration of both the antibodies with radiation increased the radiosensitivity of U87MG, resulting in a significant delay of subcutaneous (s.c.) tumour growth. Furthermore, the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
56
2
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 34 publications
13
56
2
1
Order By: Relevance
“…28 Consistent with our results, coadministration of nimotuzumab increased the radiosensitivity of subcutaneous U87MG tumors, resulting in a significant delay in tumor growth. Furthermore, the addition of nimotuzumab to radiation reduced the size of tumors formed by U87MG cells in the brain to a greater extent than did radiation alone, and it inhibited by 40%-80% the increased tumor cell invasion provoked by radiotherapy as well as promoted tumor cell apoptosis.…”
Section: Preclinical Datasupporting
confidence: 91%
“…28 Consistent with our results, coadministration of nimotuzumab increased the radiosensitivity of subcutaneous U87MG tumors, resulting in a significant delay in tumor growth. Furthermore, the addition of nimotuzumab to radiation reduced the size of tumors formed by U87MG cells in the brain to a greater extent than did radiation alone, and it inhibited by 40%-80% the increased tumor cell invasion provoked by radiotherapy as well as promoted tumor cell apoptosis.…”
Section: Preclinical Datasupporting
confidence: 91%
“…Temozolomide was purchased from Schering-Plough (stock solution 150 mmol/L in DMSO). The humanized anti-EGFR mAb nimotuzumab was generated at the Center of Molecular Immunology [11,12]. All the primary and secondary antibodies were purchased from commercial sources as listed: rabbit polyclonal EGFR antibody to total EGFR (Santa Cruz Biotechnology), mouse monoclonal antibody MIB-1 to Ki-67 (DakoCytomation), rat monoclonal anti CD31/ PECAM-1 antibody (BD Pharmingen), mouse monoclonal antibody to CD133/1 (AC133) (Miltenyi Biotec).…”
Section: Methodsmentioning
confidence: 99%
“…For immunohistochemistry, tissue sections (thickness of 8 µm) were immunostained according to standard protocols. To analyze the proliferative activity of the tumor cells, sections were stained with the MIB-1 antibody (1:50) against the Ki-67 as described previously [11]. The percentage of MIB-1-positive nuclei was determined by counting immunoreactive tumor cell nuclei in at least 5 high-power fields in the most actively proliferating tumor area.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…18 It has been suggested that brain tumor growth is dependent on the presence of a cancer stem cell niche, and, consequently, the ability to target cancer stem cells may represent an essential property of nimotuzumab. 18 The antibody has also been extensively evaluated in the clinical setting in patients bearing advanced head and neck, glioma, lung, esophageal, pancreatic, and gastric cancer, among others. 19,20 Nimotuzumab currently has marketing approval for the treatment of advanced head and neck, glioma, and esophageal cancer patients in combination with irradiation or chemo-radiotherapy.…”
Section: Introductionmentioning
confidence: 99%